Corrosion Mechanism of MgO–CMA–C Ladle Brick with High Service Life. Issue 2 (4th November 2019) - Wöhrmeyer, Christoph; Gao, Simon; Ping, Zhenfeng; Parr, Christopher; Aneziris, Christos G.; Gehre, Patrick
Abstract : Carbon‐bonded magnesia and magnesia alumina carbon (MAC) bricks have been used in the sidewalls and bottom of steel ladles for over 20 years. Due to the increasing ratio of scrap to steel, higher working temperature, and prolonged refining time, steel producers seek refractories with enhanced service lifetime. Therefore, a new generation of MgO–C bricks with addition of calcium magnesium aluminate (CMA) aggregates is tested in a ladle lining of an integrated steel shop for 138 cycles. The corrosion mechanisms are evaluated by digital light microscopy and with scanning electron microscopy (SEM) equipped with energy‐dispersive X‐ray spectroscopy (EDS). The industrial trial tests reveal the formation of a slag coating at the hot face, leading to a much slower corrosion rate compared with a common MgO–C lining. The dissolution of the CMA aggregates and MgO grains results in a significant change of the slag chemistry and viscosity causing a reduced infiltration and corrosion behavior of the ladle slag. Also, the ability of bonding iron plays a major role, leading to the formation of brownmillerite phase in the protective slag coating on top of the bricks. Abstract : A newly developed MgO–CMA–C brick is tested as part of a lining in a 120 t steel‐refining ladle in an integrated steel shop. After 138 cycles, a slag coating is formed on the hot face and the corrosion rate is much slower compared with a common MgO–C brick. The formation mechanism of the protective slag layer is investigated.